Atom probe analysis of ex-situ gas-charged stable hydrides - Haley, D; Moody, M; Bagot, P (Cambridge University Press, 2017)
In this work we report on the atom probe tomography analysis of two metallic hydrides, formed by pressurised charging using an ex-situ hydrogen charging cell, in the pressure range of 200-500 kPa (2-5 bar). Specifically we report on the deuterium charging of Pd/Rh and V systems. Using this ex-situ system, we demonstrate the successful loading and subsequent atom probe analysis of deu- terium within a Pd/Rh alloy, and demonstrate that deuterium is likely present within the oxide-metal interface of a native oxide formed on vanadium. Through these experiments, we demonstrate the feasibility of ex-situ hydrogen analysis for hydrides via atom probe tomography, and thus a practical route to 3D imag- ing of hydrogen in hydrides at the atomic scale.